Metode Pembelajaran dalam Perspektif Filsafat Pendidikan Islam di MI Muhammadiyah Gedongan - Mujiburohman, Mujiburohman; Sangadah, Siti (Lembaga Yasin AlSys, 2025)
This study aims to explore learning methods reviewed from the Philosophy of Islamic Education at Madrasah Ibtidaiyah Muhammadiyah Gedongan. The research method used is qualitative with a descriptive approach. Data were collected through direct observation, interviews with teachers and principals of the madrasah, and analysis of related documents. The results of the study indicate that Madrasah Ibtidaiyah Muhammadiyah Gedongan applies learning methods based on Islamic values, such as simplicity, honesty, and sincerity. Teachers at Madrasah Ibtidaiyah Muhammadiyah Gedongan prioritize approaches that emphasize moral and ethical values ​​in teaching. This study is expected to contribute to the development of learning methods based on Islamic values ​​in the Islamic education environment in Indonesia.